Soils dedicated to cattle rearing in Cuba: characteristics, management, opportunities and challenges - Lok, Sandra (Cuban Journal of Agricultural Science, 2016)
This study reviews the state of soils dedicated to cattle rearing in Cuba, opportunities for a proper use and main challenges to guarantee their improvement and conservation. It is highlighted the progressive deterioration and the factor or factors that limit in 90.6 % the usable agricultural area of the main cattle enterprises from the country. An amount of 45 % has low natural fertility and 30.3% have low effective depth. This study shows the advances of agro-ecological management of soils and its maintenance and improvement may be possible if cultural practices that benefit their processes and functions are implemented. In addition, it is reported the main studies conducted in this subject during the last years, and challenges for research are stated, as well as the development of knowledge on soil in cattle rearing areas. Key words: soils, cattle rearing, opportunities, challenges